2019
DOI: 10.1111/cod.13289
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of contact allergens in Thailand: A 12‐year retrospective study

Abstract: Background: Contact allergen prevalences often change. Continual surveillance is necessary to detect trends in sensitization rates and emerging allergens.Objective: To identify the prevalence of, and trends in, the positive reactions to each allergen in the baseline series during a 12-year period in Thailand. Methods: The medical records of 2803 patients who underwent patch testing at the Contact Dermatitis Clinic, Siriraj Hospital, between 2006 and 2018, were retrospectively reviewed. The baseline series used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 31 publications
4
36
1
1
Order By: Relevance
“…Presenting the largest dataset on patch test results with MCI/MI and MI from Turkey, this study highlights some similarities and differences from previous reports on this topic. First of all, many studies on MCI/ MI sensitization reported a clear female preponderance 10,12,16,26,[35][36][37] and a high percentage of patients aged over 40 years. 26,35,38 The present study, however, shows an almost equal sensitization share in male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presenting the largest dataset on patch test results with MCI/MI and MI from Turkey, this study highlights some similarities and differences from previous reports on this topic. First of all, many studies on MCI/ MI sensitization reported a clear female preponderance 10,12,16,26,[35][36][37] and a high percentage of patients aged over 40 years. 26,35,38 The present study, however, shows an almost equal sensitization share in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Consequently, the use of MCI/MI and MI in leave-on cosmetics was prohibited in Europe in 2016 and 2017, respectively, 22,23 and in 2018 the concentration of MI in rinse-off cosmetics was reduced by the European Commission to the same level as MCI/MI, ie, 15 ppm. 24 The introduction of similar legislative measures around the world led to an observable decrease in the incidence of non-occupational ACD due to isothiazolinones, mainly from cosmetic products, 12,16,25,26 while an increase in occupational ACD was observed in some countries after the epidemic due to the lack of legal restrictions of the use of isothiazolinones in industrial products. 26 There are only limited data on ACD from MCI/MI and MI in Turkey, 27,28 where MCI/MI and MI up to 15 ppm and 100 ppm, respectively, are currently allowed only in rinse-off cosmetics.…”
mentioning
confidence: 99%
“…Hair dyes have been reported to be important contact allergens, some of which are categorized as strong sensitizers . Sensitization to hair dyes, namely p ‐phenylenediamine (PPD), remains an important cause of allergic contact dermatitis (ACD) in many countries . Market surveys of hair coloring products suggest that the constituents used vary according to geographic region .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Sensitization to hair dyes, namely p-phenylenediamine (PPD), remains an important cause of allergic contact dermatitis (ACD) in many countries. 6,7 Market surveys of hair coloring products suggest that the constituents used vary according to geographic region. [8][9][10] For example, the primary intermediate PPD is more commonly used in Thailand 8 and the United States, 10 whereas toluene-2,5-diamine (sulfate) (TDA) is more popular in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In Istanbul/Turkey, the prevalence of MI sensitisation also decreased from 9.4% in 2016 to 5.6% in 2018 [102]. In Thailand, an epidemic of MI sensitisation was also observed [103]. Although Thailand followed the EU regulation of cosmetic MI exposure, a market survey indicated the prolonged presence of MCI/MI and MI preserved products, respectively, even after regulation [104].…”
Section: Preservativesmentioning
confidence: 99%